All-Optical Control and Switching Dynamics of Dissipative Kerr Soliton and Perfect Soliton Crystals - Xueying Jin; Qinglin Fang; Xin Xu; Liandong Yu; Keyi Wang; Haojie Xia (Ultrafast Science)
Dissipative Kerr solitons in optical microcavities enable various stable states involving multi-soliton and perfect soliton crystal (PSC), leading to widespread applications. However, the triggering condition and switching dynamics of the PSC and multi-soliton states (MSs) remain unexplored, which makes it challenging to selectively trigger the PSC/MS state for distinct area. Here, we theoretically and experimentally investigate the realization and switching of multi-/single-soliton and PSC states by engineering the periodic intracavity potential field constructed by control laser in a high-Q microrod cavity. We show that, by varying the parameters of the control laser, the PSC and multi-/single-soliton states can be selectively excited, and the soliton dynamics depends on the chaotic regime. We establish a fundamental link between the PSC switching behavior with the transient chaotic regime. Using such relation, we also demonstrate the switching and dynamical phenomena involving the conversion between PSC and MS, and soliton crystal melting and recrystallization. Our work provides additional routes for manipulation of soliton temporal and spectral profiles in optical microcavity systems and enables soliton generation on demand with desired states inside a single device.